BRAND EQUITY, SERVICE QUALITY, TRUSTWORTHINESS AND CONSUMER LOYALTY AFFECTING TO STAND-ALONE COFFEE HOUSES IN CHIANGMAI. - Ditajan, Nipawan; Yawila, Lasda; Sittioum, Rattana (Academic Journal Phranakhon Rajabhat University, 2022)
The purposes of this research were to investigate: 1) the brand equity affecting customer loyalty to stand-alone coffee houses in Chiangmai, 2) the influence of service quality affecting customer loyalty to stand-alone coffee houses in Chiangmai, and 3) the brand trust affecting customer loyalty to stand-alone coffee houses in Chiangmai. In this study, the samples were 385 customers living or traveling in Chiangmai. The instrument used for data collection was questionnaire. The data were analyzed and evaluated by descriptive statistics including percentage, frequency, standard deviation, and multiple linear regression. The results of this research revealed that: 1) brand equity in the aspect of brand awareness, quality awareness, brand association, and brand loyalty affected customers’ brand loyalty to stand-alone coffee houses in Chiang Mai at the statistical significance level of 0.05 and was able to predict at 69.60 percent. 2) The quality of service, concrete service, reliability, customer response, necessity, and expectation affected customers’ brand loyalty to stand-alone coffee houses in Chiang Mai at the statistical significance level of 0.05 and was able to predict at 77.70 percent, and 3) The brand trust in the aspect of reality, understanding, service, and loyalty with practice affected customers’ brand loyalty to stand-alone coffee houses in Chiang Mai at the statistical significance level of 0.05 and was able to predict at 77.70 percent.